29.3k views
5 votes
Which transformations are needed to transform the graph of y = f(x) to g(x) = -f(x - 1) + 3

1 Answer

6 votes

Step-by-step explanation:

Lets's solve this step by step. Here we have a function:


y=f(x)

So:

Step 1. Reflection across the x-axis:


y=-f(x)

Step 2. Shifting 1 unit to the right


y=-f(x-1)

Step 3. Shifting 3 unit up


y=-f(x-1)+3

Finally:


g(x)=-f(x-1)+3

So the graph of f has been reflected across the x-axis, shifted 1 unit to the right and 3 units up to become the graph of g.

User Vincent Koeman
by
4.4k points